2013
DOI: 10.4049/jimmunol.1201133
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Skews Human Macrophage Polarization through HTR2B and HTR7

Abstract: Besides its role as a neurotransmitter, serotonin (5-hydroxytryptamine, 5HT) regulates inflammation and tissue repair via a set of receptors (5HT1–7) whose pattern of expression varies among cell lineages. Considering the importance of macrophage polarization plasticity for inflammatory responses and tissue repair, we evaluated whether 5HT modulates human macrophage polarization. 5HT inhibited the LPS-induced release of proinflammatory cytokines without affecting IL-10 production, upregulated the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
126
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(153 citation statements)
references
References 50 publications
15
126
1
2
Order By: Relevance
“…First, Htr2b expression has been detected in newborn brain microglia [40] although it remains low in basal conditions [12,8,7,31]. Htr2b is also highly expressed in peripheral macrophages [14]. Htr2b mRNA expression was restricted to CD11b-positive cells purified from spinal cord and brainstem, thus originating from mononuclear phagocytes, either microglia or infiltrating monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, Htr2b expression has been detected in newborn brain microglia [40] although it remains low in basal conditions [12,8,7,31]. Htr2b is also highly expressed in peripheral macrophages [14]. Htr2b mRNA expression was restricted to CD11b-positive cells purified from spinal cord and brainstem, thus originating from mononuclear phagocytes, either microglia or infiltrating monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 2B R is expressed in microglia in the CNS [40], with expression in other cell types including brain serotonin neurons [16]. In human peripheral macrophages, 5-HT 2B R mediates the response to serotonin by skewing macrophages to a M2, anti-inflammatory, phenotype [14]. More relevant to ALS, we showed that 5-HT 2B R is the major serotonin receptor expressed on perinatal microglia and regulates chemotaxis of microglial processes in response to serotonin [40].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Data are representative of three separate experiments. recently that serotonin specifically modulates macrophage polarization by promoting acquisition of an anti-inflammatory state, which is characterized by inhibition of LPS-induced release of IL-12 and TNF-a by M-CSF-treated (M2) macrophages and downregulation of genes associated with an M1 phenotype (including MMP12 and CCR2) (36,37). The differential expression of 5HT2B and 5HT7 serotonin receptors on M2 and M1 macrophages may be important for determining the effects of serotonin in monocyte subsets (37).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 7 receptors are also found on macrophages and have been implicated as a potential target for treating intestinal inflammatory disorders. 59,60 Serotonin induces desensitization (tachyphylaxis) at different rates and magnitudes in different tissues and this is the case with 5-HT 4 receptor agonists as highlighted by prucalopride desensitizing pig atrium but not pig stomach 5-HT 4 receptors. 61 Different GRKs are associated with 5-HT 4 receptor desensitization depending on the tissue type in the rat and significantly these GRKs are not necessarily those predicted by studies using recombinant proteins expressed in cell culture.…”
Section: Discussionmentioning
confidence: 99%